2018
DOI: 10.1002/aelm.201800131
|View full text |Cite
|
Sign up to set email alerts
|

Paper‐Based Resistive Networks for Scalable Skin‐Like Sensing

Abstract: user interface. In other words, increasing resolution or adding sites for the detection of touch, generally requires augmenting the number of interconnects. With the exception of using a single electrode-based sensing technique to make natural and inanimate objects become user interfaces, there has been a lack of effort in the reduction of the number of wired leads required for scalable sensing of touch. [9] In contrast to electronic touch sensors, skin on humans/vertebrates uses hierarchical neural networks t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The reason of the interest in paper materials is related to its unique combination of properties, like biodegradability, biocompatibility, and renewability, thus reducing waste production, important aspects in an environmental-friendly manufacturing context [1]. Paper-based substrates show an intrinsic versatility since different kind of paper can be used as suitable materials depending on the application, from printer paper [2,3], glossy brochure paper, newspaper, cardboard [4] to photopaper [5], and chromatographic paper [6]. Being a disposable material, paper-based sensors have proven their validity in studies of biological samples in laboratories, but they can show their usefulness in resource-limited situations owing to low-cost, robustness and ease-of-disposal, simply burning the device in presence of biological samples avoiding sterilization [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The reason of the interest in paper materials is related to its unique combination of properties, like biodegradability, biocompatibility, and renewability, thus reducing waste production, important aspects in an environmental-friendly manufacturing context [1]. Paper-based substrates show an intrinsic versatility since different kind of paper can be used as suitable materials depending on the application, from printer paper [2,3], glossy brochure paper, newspaper, cardboard [4] to photopaper [5], and chromatographic paper [6]. Being a disposable material, paper-based sensors have proven their validity in studies of biological samples in laboratories, but they can show their usefulness in resource-limited situations owing to low-cost, robustness and ease-of-disposal, simply burning the device in presence of biological samples avoiding sterilization [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to emphasize here that the electrical impedance measurements of human skin may show variations from trial to trial within an individual participant and between different participants as reported for finger skin in earlier studies. [ 48 ] The impedance magnitude of skin, similar to its resistance, was found to be higher when measured with metal electrodes compared to hydrogel electrodes due to the effect of electrode polarization impedance. Moreover, the electrode polarization impedance caused phase lag in the impedance response.…”
Section: Resultsmentioning
confidence: 99%
“…P aper continues to receive attention as a material for electronics and robotics due to its low cost, recyclability, and foldability. For electronics, many state-of-the-art paperbased devices have included sensors, [1][2][3][4][5][6] methods of energy storage, [7][8][9] transistors, [10][11][12][13] and electrochemical detectors. [14][15][16] Paper-based robots benefit from the folding and cutting techniques of paper-origami/kirigami-to achieve large deformation.…”
Section: Introductionmentioning
confidence: 99%